ChemInform Abstract: Synthesis of Aryl(di)azinylmethanes and Bis(di)azinylmethanes via Transition‐Metal‐Catalyzed Cross‐Coupling Reactions. Issue 1 (January 2015) - De Houwer, Johan; Maes, Bert U. W.
Abstract Review: [51 refs.